Procedural features of the consideration and resolution by the courts of cases related to the establishment of the origin of children - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2020)
The article analyzes some of the procedural features of the consideration by the courts of cases of establishing and contesting of paternity. In particular, the author considers such issues as whether it is lawful to refuse to accept a claim for establishing paternity if a specific person is recorded by the child’s father; whether it is possible to leave a statement of claim without movement due to non-attachment of evidence to it; who has the right to apply to the court with a claim for establishing (contesting) of paternity and what is the procedural position of the child in these cases; what are the standards of evidence in cases involving the identification of children. On this basis, the article proposes to improve the material and procedural legislation, as well as the practice of its application.